Data from: Getting chased up the mountain- high elevation may limit performance and fitness characters in a montane insect - Dahlhoff, Elizabeth P.; Dahlhoff, Victoria C.; Grainger, Corinne A.; Zavala, Nicolas A.; Otepola-Bello, Dami; Sargent, Brynn A.; Roberts, Kevin T.; Heidl, Sarah J.; Smiley, John T.; Rank, Nathan E. (Dryad, 2019)
1. Climate change is expected to shift species distributions as
populations grow in favorable habitats and decline in harsh ones. Montane
animals escape warming conditions at low elevation by moving upslope, but
may be physiologically constrained by conditions there. Effects of
elevation were studied for montane populations of the leaf beetle
Chrysomela aeneicollis, where allele frequencies at nuclear genes and the
mitochondrion vary along latitudinal and altitudinal gradients. 2. A
population presence survey conducted along a steep altitudinal transect
(1600-3800 m) from 1981 to 2018 revealed that populations expand to low
elevation following wet winters and retreat during drought. Quantitative
surveys of a 45-site population network conducted from 2012-2018 along
multiple altitudinal transects shows that when beetles are abundant,
population size peaks at 3135 m, highest altitude populations are at the
southern edge of the range, and populations decline and extirpate during
drought, especially at low elevation. 3. To examine effects of elevation
on measures of performance and fitness, beetles from a
genetically-introgressed population (Bishop Creek- BC) were examined. In
nature, fecundity of females transplanted along natural altitudinal
transects was measured, as was thorax cytochrome c oxidase (CytOx)
activity. To examine effects of environmental hypoxia independent of other
factors limiting persistence at high elevation, development rate and
activity of malate dehydrogenase (MDH) were measured for larvae reared
under otherwise common garden conditions at low (1250 m) and high (3800 m)
elevation. 4. In nature, fecundity declined with increasing elevation,
independent of air temperature. CytOx activity was higher at high than low
elevation, especially for individuals possessing genotypes of southern
origin. Laboratory-reared larvae with southern mitochondrial haplotypes
developed equally well at both elevations, but larvae with northern
haplotypes developed more slowly at high elevation. MDH activity showed a
similar pattern, suggesting that slower development rates at high
elevation may be due to reduction in metabolic rate. 5. These findings
suggest that physiological effects of environmental hypoxia may contribute
to other factors known to restrict insects’ ability to persist at high
elevation, ultimately disrupting associated ecological communities.
However, some populations may possess genetic variation that allows for
local adaption to high elevation.
FIG 1. Beetle elevation limits and site snow depthThis is an Excel file
that contains data from Fig 1. Fig 1A data were determined from long-term
population surveys in Big Pine Canyon. 1B data was obtained from
California's Department of water resources website for the snow
logger nearest these sites.FIG 1 data Dahlhoff et al. FE.xlsxFIG 2. Beetle
abundance by elevationExcel file with 2 tabs. First tab is maximal
abundance by site in 2012. Second tab shows statistical output of final
analysis.FIG 2 data.xlsxFIG 3. Abundance over time during droughtExcel
file. Tab 1- raw data. Tabs 2 and 3 for conversion to analysis by
Permanova. Tab 4 permanova output.FIG 3 data.xlsxFIG 4. Fecundity by
elevationExcel file. Tab 1 is final data used in figure. Tab 2 is Jmp
output. tab 3 is models used to ascertain importance of temperature. Tab 4
is complete raw data with behavior.FIG 4 data.xlsxPhysiological and lab
data reported in Figs 5 and 6These are raw data and Jmp outputs for CytOx
data, development rate data, and MDH data reported in paper.Physiological
and lab data (Fig 5-6).xlsx
Keywords: willow beetles; Altitude; Hypoxia; metabolic enzymes; development rate; Chrysomela aeneicollis